PENGARUH METODE KOAGULASI, SEDIMENTASI DAN VARIASI FILTRASI TERHADAP PENURUNAN KADAR TSS, COD DAN WARNA PADA LIMBAH CAIR BATIK - Rahmah Rahmah; Surahma Asti Mulasari (CHEMICA: Jurnal Teknik Kimia, 2016)
Batik industry in Indonesia increased so that the impact resulting from the production process in the form of wastewater is increasing. Wastewater disposal after staining and washing process without processing will improve environmental contamination such as TSS, COD, and color levels. The problems of batik wastewater contamination can be resolved by the treatment of wastewater in chemistry and physics. One way batik wastewater treatment is coagulation, sedimentation, and filtration. Filtration media are used as filter media is activated charcoal, quartz sand, and zeolite. The purpose of this research is to determine the effect of the coagulation, sedimentation, and filtration variation method on decreased levels of TSS, COD, and color in the wastewater of batik. The type of this research was a true experiment with a pre-test post-test group design. Samples of this research were batik wastewater with levels of TSS, COD, and the color is 818 mg/ l, 1133.57 mg/ l, and 100 TCU. Data was analyzed using one-way ANOVA. The result after treatment of coagulation, sedimentation, and filtration variety occurs decreased levels of TSS, COD, and color on filtration variation of activated charcoal and quartz sand, respectively for 99.8%, 99.49% and 99.6%, variation of the zeolite filtration and activated charcoal was, 99.6%, 92.31%, and 99.5%, and variations in zeolite filtration and quartz sand were 99.7%, 89.92%, and 99.3%. Based on the statistical test using the ANOVA test on the TSS levels were obtained p= 0.190, while the COD was obtained a value of p= 0.008 and the value of color was p= 0.017. The methods of coagulation, sedimentation, and filtration variation using activated charcoal, quartz sand, and zeolite can reduce TSS, COD, and color levels. There is no difference between the variation of filtration to decrease levels of TSS, while there is a difference between the variation filtration to decreased levels of effluent COD and color Batik.